IMPLEMENTASI METODE EKSPERIMEN DALAM PEMBELAJARAN IPA UNTUK MEMOTIVASI SISWA - Desta Putri Awalia; Sheryl Mutiara Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Science learning in Elementary Schools plays an important role in shaping students' initial understanding of scientific principles, as well as instilling scientific attitudes and problem-solving skills. This study aims to explore the extent to which the application of experimental methods can improve students' learning motivation. The study used a literature review method with a qualitative descriptive approach, referring to relevant journals, articles, and academic books published in 2016–2024 that have been reviewed. The analysis was carried out by grouping findings based on themes such as the impact of experiments on learning motivation, conceptual understanding, and science process skills. The results showed that the experimental method significantly increased students' interest, curiosity, and active participation in learning. In addition to helping understand abstract concepts, this method also develops skills such as observing, recording, and concluding. Thus, the experimental method is proven to be effective, applicable, and relevant to improve motivation and the quality of science learning at the Elementary School level optimally and meaningfully.